Variable-depth curved layer fused deposition modeling of thin-shells. (June 2019) - Chen, Lufeng; Chung, Man-Fai; Tian, Yaobin; Joneja, Ajay; Tang, Kai
Highlights: A complete framework of a variable-depth curved layer multi-axis additive manufacturing process targeted at thin-shells. An improved variable-thickness mesh offsetting operation for solid fabrication. A novel variable-depth curved layer slicing algorithm for a general curved layer fused deposition modeling (CLFDM) process. A boundary-conformed print path generation scheme that synchronizes nozzle movements and extrusion operation. Abstract: This paper presents a framework containing thin-shell modeling, curved layer slicing, and process planning algorithms for a variable-depth curved layer multi-axis additive manufacturing process for printing thin-shells. Currently, to print a thin-shell part such as a blade, under the popular paradigm of fused deposition modeling (FDM), the traditional type of flat layer three-axis printing suffers from the severe stair-step effect on the printed surface. Even with a more advanced multi-axis 3D printer that enables curved layer FDM (CLFDM), at present, only uniform-thickness layers are supported, which again is unable to resolve the pronounced stair-step problem. However, by allowing the sliced layers to have variable thicknesses and adjusting the build direction adaptively with respect to the surface normal, the stair-step effect can be either completely eradicated or reduced to the minimum. While the presented framework is targeted specifically at the algorithmic aspect of this ideal five-axis CLFDM printing, we have also performed physical experiments on a prototype five-axis FDM printer. The experimental results have validated the feasibility of our proposed methodology and demonstrated its potential in many applications.